To Study Insulin Resistance in Type 2 Diabetes Mallitus by Homa-IR Score - Purohit, Ashish; Tiwari, Varsha (International Journal of Medical Research and Review, 2015)
Introduction: Insulin resistance precedes and strongly predicts the development of type 2 diabetes mellitus, estimation of insulin resistance was helpful in detection of early complications and selecting the treatment options, hence the present study was planned. HOMA estimated insulin resistance is an independent predictor of cardiovascular disease in type-2 diabetic subjects. Materials and Methods: A case control study was carried out in the Department of Medicine comprising 50 newly diagnosed type 2 diabetes mellitus patients and 50 healthy controls. The HOMA IR method was used in the present study for estimation of insulin resistance as it is simple and appropriate. Results: median value of fasting plasma insulin in cases was 7.45µU/ml with mean 10.53 ± 9.42µU/ml while in control was 7.19 with mean 7.43 ± 2.26µU/ml (p value 0.025856) and of fasting plasma glucose was 146 mg/dl with mean 164.12 + 54.43mg/dl and controls had median 112 with mean 110.6 + 7.07mg/dl (p value 0.000000). The median value of HOMA IR score is 2.91 in cases with mean value of 4.15 ± 3.56 and controls of 1.97, mean 2.03 + 0.64 (p value .000072). The most prevailing complications were retinopathy 26%(13,p<0.01) and neuropathy26%(13,P<0.01). Conclusion: HOMA-IR score in present study was higher, it indicates that IR was higher in Patient of T2 DM in Gwalior Chambal zone as compared to other countries and high score is associated with increase risk of diabetic retinopathy, neuropathy, nepropathy, CAD, Peripheral vascular disease.